Legal Protection for Illegal Migrant Domestic Workers under the ASEAN Regulations and its Implication for Indonesia - Muthia, Arini Azka (Indonesian Journal of International Law, 2020)
Domestic work is an essential source of livelihood for women and men in Southeast Asia and requires legal protection, including for illegal migrant domestic worker. The ASEAN Consensus on Protection and Promotion of the Rights of Migrant Worker 2017 regulates the protection of migrant workers, including illegal migrant workers in the domestic sector. This research discusses the implications of the ASEAN Consensus on the Protection and Promotion of the Rights of Migrant Worker 2017 for the ASEAN member countries, particularly Indonesia. This research applies a juridical-normative approach focusing on the legal materials related to the protection of domestic workers. This research also applies the statute approach. The data are analyzed qualitatively. This research concludes that the ASEAN Consensus 2017 requires close cooperation between ASEAN countries in resolving cases of illegal migrant workers through preventive measures under national laws, regulations and policies that apply in ASEAN Member Countries. Indonesia is expected to be able to implement what was agreed in the ASEAN Consensus 2017 on national legislation and other domestic policies related to the protection and promotion of migrant workers’ rights in the domestic sector. Efforts in implementing the ASEAN Consensus 2017 on migrant workers for Indonesia can be pursued in two ways, efforts to improve internally and externally.